Monitoring basic skills acquisition through rapid learning assessments: A case study from Peru - Abadzi, Helen; Crouch, Luis; Echegaray, Marcela; Pasco, Consuelo; Sampe, Jessyca (PROSPECTS, 2005)
KerkoCite.ItemAlsoKnownAs: 10.1007/s11125-005-1817-3 2339240:QDJBCG9B 2405685:KCL8RYGR

National Policies that Connect ICT-Based Education Reform to Economic and Social Development - Kozma, Robert B. (Human Technology: An Interdisciplinary Journal on Humans in ICT Environments, 2005)
Information and communication technology (ICT) is a principal driver of economic development and social change, worldwide. In many countries, the need for economic and social development is used to justify investments in educational reform and in educational ICT. Yet the connections between national development goals and ICT-based education reform are often more rhetorical than programmatic. This paper identifies the factors that influence economic growth and shows how they supported economic and social development in three national case studies: Singapore, Finland, and Egypt. It describes a systemic framework of growth factors and types of development that can be used to analyze national policies and connect ICT-based education reform to national economic and social development goals. And it discusses how the coordination of policies within and across ministries can support a nation’s efforts to improve economic and social conditions. The paper highlights special concerns and challenges of developing countries.
shortDOI: 10/gf54xx KerkoCite.ItemAlsoKnownAs: 10.17011/ht/urn.2005355 10/gf54xx 2339240:U6EMQ8ZJ 2339240:XP4CBBBW 2405685:4IF64UER 2405685:MUCISL2Q